2021
DOI: 10.1016/j.drugpo.2020.102978
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of qualitative evidence on barriers to and facilitators of the implementation of opioid agonist treatment (OAT) programmes in prisons

Abstract: Background: Opioid Agonist Treatment (OAT) programmes are regarded as a gold standard treatment for people living with Opioid Use Disorders (OUDs). However, OAT programmes are often unavailable or poorly implemented in prisons, in spite of the large numbers of people living with OUDs and the high risk of HIV transmission in prison settings. Unusually, this systematic review synthesizes qualitative evidence relating to barriers to, and facilitators of, the implementation of OAT programmes in prisons in high-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…The experiences of these early adopters can provide implementation success stories and guidance on program structure to other carceral programs considering adopting OAT. Consistent with prior research, we find that OAT provision is challenged by logistic constraints, stigma and difficulty with reentry services [19–21]. Participants in our study offer ways to overcome such barriers, including partnering with community OAT providers, eliminating unnecessary eligibility criteria and utilizing peer navigators.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The experiences of these early adopters can provide implementation success stories and guidance on program structure to other carceral programs considering adopting OAT. Consistent with prior research, we find that OAT provision is challenged by logistic constraints, stigma and difficulty with reentry services [19–21]. Participants in our study offer ways to overcome such barriers, including partnering with community OAT providers, eliminating unnecessary eligibility criteria and utilizing peer navigators.…”
Section: Discussionsupporting
confidence: 81%
“…Lessons learned from innovators and early adopters can contribute to the continued diffusion of an innovation, as the majority of adopters seek implementation success stories, evidence of effectiveness and pressure from peers to motivate adoption. Single‐site studies of OAT implementation among innovators and programs that only provide medication maintenance identify space and staffing constraints, stigma and difficulty in arranging post‐incarceration care as key challenges to implementation [19–21].…”
Section: Introductionmentioning
confidence: 99%
“…In both of the study prisons with MMT programmes, many prisoners indicated that they had experienced stigma associated with their participation in these programmes as indicated by previous study (Komalasari et al, 2020). This was confirmed by some health-care staff in the general methadone prison and has also been recognised in studies in other locations (Woo et al, 2017;Carlin, 2005;Mitchell et al, 2009).…”
Section: Discussionsupporting
confidence: 69%
“…In common with other studies (Sto ¨ver and Kastelic, 2016; Komalasari et al, 2020;Komalasari et al, 2021), this study found considerable misunderstandings relating to the use of methadone programmes as part of an HIV harm reduction strategy amongst both prison staff and prisoners and across all three study prisons. The idea that methadone is simply another type of illicit drug, was prevalent amongst most prison officers and some health-care staff, again across all three prisons.…”
Section: Discussionsupporting
confidence: 69%